International Experience of Ensuring the Competitiveness of Regional Economies with Instrumental Functions of the Cluster Approach - Nekrasova, Marina L.; Vronskaya, Maria V.; Demin, Sergey S.; Zainasheva, Zarima G.; Sharipova, Vlada V.; Khannanova, Tatyana R.; Tkachev, Sergey V. (International Review of Management and Marketing, 2016)
As the results of the study, the clusters are the driving force for increasing exports and attracting foreign investment. Because of this, the authors note that you need to pay special attention to the need for enhanced clustering spatially localized economies. Holding company has a special role in shaping the country's budget, therefore, exploring new forms of economic relations generated by the cluster, we consider it necessary to consider the formation of the holding clusters that combine the features of the holding company as a conglomerate of different entities and cluster technologies developed on the basis of flow knowledge from one company to another. Through the creation of an extensive system of participation in a cluster ensures the stability of the whole group, because in this case significantly reduced business risks. Keywords: region, cluster, competitiveness, state, regional institutions JEL Classifications: F00; P25